2001
DOI: 10.1093/nar/29.21.4361
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 induces collagenase-3 (MMP-13) promoter activity in stably transfected chondrocytic cells: requirement for Runx-2 and activation by p38 MAPK and JNK pathways

Abstract: Osteoarthritic chondrocytes secrete matrix metalloproteinase-13 (MMP-13) in response to interleukin-1 (IL-1), causing digestion of type II collagen in cartilage. Using chondrocytic cells, we previously determined that IL-1 induced a strong MMP-13 transcriptional response that requires p38 MAPK, JNK and the transcription factor NF-kappaB. Now, we have studied the tissue-specific transcriptional regulation of MMP-13. Constitutive expression of the transcription factor Runx-2 correlated with the ability of a cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
170
1
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(193 citation statements)
references
References 35 publications
19
170
1
3
Order By: Relevance
“…Mengshol et al reported similar results (35). Investigators in previous studies have concluded that signal transduction pathways modulating transcription factors such as AP-1, RUNX, and NF-B regulate expression of MMP-13 (11,12,(34)(35)(36)(37)(38)(39). We observed that double mutation of 2 C/EBP␤ binding motifs in this domain diminished promoter activity to basal levels and abolished the promoter's response to C/EBP␤ overexpression ( Figures 4C and D).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Mengshol et al reported similar results (35). Investigators in previous studies have concluded that signal transduction pathways modulating transcription factors such as AP-1, RUNX, and NF-B regulate expression of MMP-13 (11,12,(34)(35)(36)(37)(38)(39). We observed that double mutation of 2 C/EBP␤ binding motifs in this domain diminished promoter activity to basal levels and abolished the promoter's response to C/EBP␤ overexpression ( Figures 4C and D).…”
Section: Discussionsupporting
confidence: 86%
“…Tardif et al reported that the Ϫ133-bp region of the promoter included high activity AP-1 and RUNX binding motifs, and that deletion to Ϫ39 bp diminished promoter activity to the basal level (34). Mengshol et al reported similar results (35). Investigators in previous studies have concluded that signal transduction pathways modulating transcription factors such as AP-1, RUNX, and NF-B regulate expression of MMP-13 (11,12,(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 66%
“…Transforming growth factor ␤ is shown to induce MMP13 gene expression but down-regulates MMP1 gene expression at the same time (34,35). Another recent study has shown that Runx-2, a tissuespecific constitutive transcription factor, is required for MMP13 expression in response to IL-1 (36). Also, MMP2 and MMP14 do not contain any AP-1 element, yet they are activated, like other MMP genes, by the same stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of MMP13 gene expression by runt-related transcription factor 2 and AP-1 sites has been described in osteoblasts, hypertrophic chondrocytes, and stably transfected chondrocytic cell lines (47)(48)(49)(50). Moreover, recent studies have shown that estrogen receptor-a can regulate the expression of MMP-13, primarily through the AP-1 transcriptional regulatory site (51) in the HIG-82 cells.…”
Section: Figurementioning
confidence: 99%